Multiple carrier-transfer pathways in a flower-like In2S3/CdIn2S4/In2O3 ternary heterostructure for enhanced photocatalytic hydrogen production. Issue 16 (17th April 2018) - Ma, Dandan; Shi, Jian-Wen; Zou, Yajun; Fan, Zhaoyang; Shi, Jinwen; Cheng, Linhao; Sun, Diankun; Wang, Zeyan; Niu, Chunming
Abstract : A novel flower-like In2 S3 /CdIn2 S4 /In2 O3 ternary heterostructure is rationally constructed for the first time, and it shows significantly enhanced photocatalytic H2 production. Abstract : A novel flower-like In2 S3 /CdIn2 S4 /In2 O3 (ICS) ternary heterostructure (HS) is rationally constructed for the first time by a series of carefully designed procedures. In2 O3 nanoflakes are the main constituent units which assemble into a flower-like skeleton structure, and CdIn2 S4 nanoparticles are in situ generated on the surface of In2 O3 nanoflakes through the transformation of CdS quantum dots (QDs) while In2 S3 nanoparticles are in situ produced at the region between CdIn2 S4 nanoparticles and In2 O3 nanoflakes resulting from a synchronous sulfuration procedure. As expected, the rationally designed ICS ternary HSs display significantly enhanced photocatalytic H2 production, especially ICS5 (sulfurized for 5 h) with the highest H2 evolution rate of 20.04 μmol h −1 (10 mg catalyst is used for photocatalytic reaction), which is 26.7 times and 2.6 times higher than that of pure In2 O3 (0.75 μmol h −1 ) and In2 S3 /In2 O3 binary HS (7.88 μmol h −1 ), respectively. The enhanced photocatalytic activity can be attributed to the multiple interfaces formed in the ICS HSs, including the CdIn2 S4 –In2 O3 interface, the In2 S3 –In2 O3 interface, and the CdIn2 S4 –In2 O3 –In2 S3 interface, which construct multiple pathways for the transfer of photogenerated charge carriers, effectively promoting the photocatalytic hydrogen production.